Analisis Hasil pembelajaran operasi pecahan di sekolah dasar SDN Sudimara 2 Ciledug - Fadel Sabil; Een Unaenah; Nabila Zahra Safira; Puji Lestari (Jurnal Pendidikan Indonesia, 2022)
This study aims that the learning process in improving learning is accompanied by learning strategies, learning strategies All of these aspects provide an important role in improving the learning outcomes of Grade 2 students at SDN SUDIMARA 2 CILEDUG in the Covid-19 Era. With the learning strategy, it is hoped that the online (Online) and Offline (Face-to-Face) learning process can be carried out well so that it can increase good learning outcomes. To conclude that a learning strategy is a pattern that is planned and determined intentionally to carry out an activity or action. Where learning is an effort by educators to help students carry out learning activities. Thus the learning strategy includes the use of approaches, methods and techniques, forms of media, learning resources, grouping of students, to realize educational interactions between educators and students, between students, and to the process, results, or impact of learning activities. In this case, the learning strategy is defined as a plan that contains a series of activities designed to achieve certain educational goals.